Virtual ARCP assessment and trainee feedback meetings: facilitating the best experience and practice. Issue 10 (December 2020) - Oeppen, R.S.; Rutherford, E.; Sadler, P.; Isaac, R.; Brennan, P.A.
Abstract: As a result of COVID-19, there has been an exponential increase in the use of remote technology for many local, regional and national meetings that would previously have been held on a face-to-face basis. Remote meetings have ensured that essential clinical, educational and strategic work can continue but it is not 'business as usual', although colleagues accept this form of communication as the new norm. In medical education and assessment, the Annual Review of Competence Progression (ARCP) meetings and other formative educational meetings are being conducted remotely. This form of communication has some advantages but may also present possible barriers for feedback and development particularly for 'trainees in difficulty' when there are concerns about progression, and when an unsatisfactory outcome has been awarded. It is also worth remembering that there may be generational differences with the ease of use of virtual meeting platforms. We present some of the important factors for optimising the panel of virtual ARCPs and discuss methods to improve feedback given remotely for trainees.